THE EFFECTS OF SUPERVISION, SOCIAL COMPETENCE, AND PROFESSIONAL COMPETENCE TOWARD THE TEACHERS PERFORMANCE OF STATE OF JUNIOR HIGH SCHOOL - Jumriati Jumriati; Suryadi Suryadi; Hasbi Sjamsir (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
The objective of this research was to know influence of supervision, social interest and professional interest to performance of public junior high school teacher in Tanjung Redeb district, Berau regency. The method of this research was correlation method. The responden in this research was all of the public junior high school teacher in Tanjung Redeb district, Berau regency. Data were collecting by using questionnaire, with four instruments such as supervision, social interest, professional interest and performance. Instruments were calibrated by using validity test and of reliability. Item validity was calculated by using correlation coefficient of product moment correlation, while the coefficient of instrument reliability was calculated by using alpha cronbach formula. The result of this research are there are positive relation supervise to teacher performance, there are positive relation social interest with teacher performance, and there are positive Influence interest of professional learn with teacher performance. Fourth of raised hypothesis were accepted, hence teacher performance can be improved through supervision, social interest and professional interest of teacher. Keywords: Performance Teacher, Supervision, Social Interest and Professional Interest of Teacher.